2014
DOI: 10.1371/journal.pone.0104996
|View full text |Cite
|
Sign up to set email alerts
|

Random Whole Metagenomic Sequencing for Forensic Discrimination of Soils

Abstract: Here we assess the ability of random whole metagenomic sequencing approaches to discriminate between similar soils from two geographically distinct urban sites for application in forensic science. Repeat samples from two parklands in residential areas separated by approximately 3 km were collected and the DNA was extracted. Shotgun, whole genome amplification (WGA) and single arbitrarily primed DNA amplification (AP-PCR) based sequencing techniques were then used to generate soil metagenomic profiles. Full and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 52 publications
0
29
0
Order By: Relevance
“…Forensic soil analyses are usually conducted by comparing questioned samples with those of known origin to evaluate whether they are similar (inclusion) or different (exclusion) based on physical characteristics (e.g., soil color, texture, consistency, density, porosity, and particle size) (2)(3)(4) and chemical properties (i.e., mineralogy and elemental composition) (1,(4)(5)(6). With the growth of molecular techniques, research has shown the potential of soil DNA profiling as a reliable method for forensic soil analyses (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). The current ecological hypothesis states that the soil type (e.g., chemical and physical properties) determines which microbes and plants occupy a particular soil (20)(21)(22) and provides the foundation for soil provenance studies to assist in intelligence gathering or forensic applications.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Forensic soil analyses are usually conducted by comparing questioned samples with those of known origin to evaluate whether they are similar (inclusion) or different (exclusion) based on physical characteristics (e.g., soil color, texture, consistency, density, porosity, and particle size) (2)(3)(4) and chemical properties (i.e., mineralogy and elemental composition) (1,(4)(5)(6). With the growth of molecular techniques, research has shown the potential of soil DNA profiling as a reliable method for forensic soil analyses (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). The current ecological hypothesis states that the soil type (e.g., chemical and physical properties) determines which microbes and plants occupy a particular soil (20)(21)(22) and provides the foundation for soil provenance studies to assist in intelligence gathering or forensic applications.…”
mentioning
confidence: 99%
“…Studies have shown the potential and effectiveness of using microbial DNA from soil to identify the origin of a soil sample (7)(8)(9)11,14,(16)(17)(18). A majority of the studies explore the bacterial 16S rRNA genes using terminal restriction length fragment polymorphism (T-RFLP) (7,9,10) or length heterogeneity polymerase chain reaction (LH-PCR) (8,23).…”
mentioning
confidence: 99%
“…The microbes and hence the microbial DNA differs in males and females and therefore after sex, the microbes in both the male and the female appear to swap, indicating that a sexual act occurred between a particular man and woman. The microbial forensics has been broadened by metagenomic analysis of the microbes from the surroundings also such as from soil [37] in case of bioterroism/murderous crimes, which may also help in collecting and corroborating evidences to correlate with the incident.…”
Section: Microbial Forensicsmentioning
confidence: 99%
“…Current efforts that have used molecular-based approaches such as DNA barcoding to document the biodiversity within a soil sample have primarily been focused on a bulk metagenomic approach [41][42][43][44][45][46][47][48][49][50]. Using conserved primers for the desired barcode regions, individual taxa can be amplified and sequenced simultaneously (i.e., massively parallel sequencing) from a single bulk soil extraction.…”
Section: Introductionmentioning
confidence: 99%